Nitrogen-related intermediate band in P-rich GaNxPyAs1−x−y alloys. Issue 1 (December 2017) - Zelazna, K.; Gladysiewicz, M.; Polak, M.; Almosni, S.; Létoublon, A.; Cornet, C.; Durand, O.; Walukiewicz, W.; Kudrawiec, R.
Abstract The electronic band structure of phosphorus-rich GaNx Py As1−x−y alloys (x ~ 0.025 and y ≥ 0.6) is studied experimentally using optical absorption, photomodulated transmission, contactless electroreflectance, and photoluminescence. It is shown that incorporation of a few percent of N atoms has a drastic effect on the electronic structure of the alloys. The change of the electronic band structure is very well described by the band anticrossing (BAC) model in which localized nitrogen states interact with the extended states of the conduction band of GaAsP host. The BAC interaction results in the formation of a narrow intermediate band (E− band in BAC model) with the minimum at the Γ point of the Brillouin zone resulting in a change of the nature of the fundamental band gap from indirect to direct. The splitting of the conduction band by the BAC interaction is further confirmed by a direct observation of the optical transitions to the E+ band using contactless electroreflectance spectroscopy.